The viability of Salam finance in the growth of agricultural production in Kano State, Nigeria - Mohammed, Ahmed Ibrahim; Ogunbado, Ahamad Faosiy; Aziz, Ahmad Bashir (2016)
Salam finance (sales contract) is a Shariah product used by Islamic financial institutions.It is a transaction in which the payment of the sold commodity is to be made at a spot or immediately after signing the sales contract, while the delivery of the commodity is at the agreed future time.The paper intents to study this Islamic mode of financing agriculture in order to see the way and manner it can enhance the agricultural output of Kano state, being the most populous and agrarian state in Nigeria.This study explores the potentialities of Salam finance.It’s role in the growth of agricultural output to meet the demand level of the state population and provide raw materials for industries. It highlights the historical background of Kano state in terms of agriculture and agribusiness.Almost, 70 percent of the population as is solidly dependent on agriculture and agribusiness as their main source of livelihood.Agriculture contributes a higher percentage to the state revenue before the discovery of petroleum.This paper recommends that, the Kano state micro finance banks, mostly the ones in rural areas should adopt Salam mode of financing.It is expected that the adoption of Salam finance will improve the supply of agricultural output, create more employment opportunities and improve local and modern industries and commerce.It will also promote sustainable growth of the Kano state economy and Nigeria in general.This is a qualitative paper in terms of methodology.